A ZIF-8 / aluminum silicate nanofiber composite membrane and preparation method thereof

By aminating and cross-linking the aluminum silicate nanofibers and growing the ZIF-8 nanolayer in situ on its surface, a ZIF-8/aluminum silicate nanofiber composite film was prepared, which solved the problem of difficult recovery of nanomaterials in powder form, and achieved strong adsorption effect on heavy metals and efficient material recovery.

CN119175084BActive Publication Date: 2025-03-14CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411676777.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The powder-like morphology of existing nanomaterials is difficult to completely separate, affecting their application in water treatment.

Method used

The aluminum silicate nanofibers were modified by amino acids and cross-linked with ethylenediaminetetraacetic acid dianhydride to form a functionalized aluminum silicate nanofiber membrane, and then the ZIF-8 nanolayer was grown in situ on the surface of the membrane to prepare a ZIF-8/aluminum silicate nanofiber composite membrane.

Benefits of technology

It achieves strong adsorption effect on heavy metals, and solves the problem of difficult recycling of nanomaterial powders, improving the practicality and economic benefits of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a method for preparing a ZIF-8 / aluminum silicate nanofiber composite membrane, comprising the following steps: (1) modifying aluminum silicate nanofibers by amino acids to obtain amino aluminum silicate nanofibers; (2) cross-linking and modifying the amino aluminum silicate nanofibers by ethylenediaminetetraacetic acid dianhydride, then filtering and forming a membrane, and washing the membrane thoroughly to obtain a functionalized aluminum silicate nanofiber membrane; (3) in-situ growing a ZIF-8 nanolayer on the surface of the functionalized aluminum silicate nanofiber membrane, and drying to obtain a ZIF-8 / aluminum silicate nanofiber composite membrane. The present invention also discloses a ZIF-8 / aluminum silicate nanofiber composite membrane obtained by the preparation method. The present invention realizes the effective compounding of aluminum silicate nanofibers and ZIF-8 nanoparticles, solves the defect that the powdered nanomaterial is difficult to recycle, and has a high adsorption efficiency for heavy metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum silicate composite membrane, in particular to a ZIF-8 / aluminum silicate nanofiber composite membrane and a preparation method thereof. Background Art

[0002] Industrial wastewater often contains a large amount of heavy metal ions. Adsorption is a common method for treating heavy metal pollution. The key to its removal effect lies in the selection of adsorbent materials. Nanomaterials have attracted great attention in the field of heavy metal adsorption due to their unique properties, such as significant small size effect, quantum size effect and large specific surface area. In particular, ZIF-8 in the metal organic framework (MOFs) family has become an important material in the field of water treatment due to its low density, ultra-large specific surface area, high porosity and rich surface functional groups. In addition, hydrated aluminum silicate nanofibers, as a new type of environmentally friendly nano mineral fiber material, are also used in the field of heavy metal adsorption due to their unique mesoporous tubular lumen, large specific surface area, rich surface groups and inner and outer surfaces with different charges. However, the powdery morphology of nanomaterials makes it difficult to completely separate them in the treatment system, which seriously affects the practical application of nanomaterials such as ZIF-8 and hydrated aluminum silicate nanofibers in water treatment. Summary of the invention

[0003] In view of the above-mentioned defects of the prior art, the present invention provides a method for preparing a ZIF-8 / aluminum silicate nanofiber composite membrane, and a ZIF-8 / aluminum silicate nanofiber composite membrane obtained by the method, which achieves a strong adsorption effect on heavy metals while solving the problem that powdered nanomaterials are difficult to recycle.

[0004] The technical solution of the present invention is as follows: A method for preparing a ZIF-8 / aluminum silicate nanofiber composite membrane comprises the following steps:

[0005] (1) Modifying aluminum silicate nanofibers by amino acids to obtain amino-modified aluminum silicate nanofibers;

[0006] (2) cross-linking and modifying the amino-modified aluminum silicate nanofibers by ethylenediaminetetraacetic acid dianhydride, then filtering and forming a membrane, and washing the membrane thoroughly to obtain a functionalized aluminum silicate nanofiber membrane;

[0007] (3) In situ growing a ZIF-8 nanolayer on the surface of the functionalized aluminum silicate nanofiber membrane, and obtaining a ZIF-8 / aluminum silicate nanofiber composite membrane after drying.

[0008] Furthermore, the step (1) specifically comprises dispersing the aluminum silicate nanofibers in dimethyl sulfoxide, uniformly dispersing by ultrasonication, and then sequentially adding amino acids and p-toluenesulfonic acid for stirring reaction, wherein the dosage ratio of the aluminum silicate nanofibers to the amino acids is 1 g: (0.5-2) g.

[0009] Furthermore, in the step (1), the stirring reaction is to stir the reaction liquid at 50-80° C. for 3-6 hours, and after the reaction, the reaction is filtered, repeatedly washed with deionized water, and dried to obtain the amino-containing aluminum silicate nanofibers.

[0010] Furthermore, the amino acid is one of glycine, alanine, valine, leucine, aspartic acid, and glutamic acid.

[0011] Furthermore, the step (2) specifically comprises dispersing the amino-silicon aluminum nanofibers in ‌N , N -dimethylformamide, ultrasonically dispersed uniformly, and ethylenediaminetetraacetic acid dianhydride was added to carry out a cross-linking reaction, wherein the amount ratio of amino-silicic acid aluminum nanofibers to ethylenediaminetetraacetic acid dianhydride was 1g: (0.2-0.6)g.

[0012] Furthermore, in the step (2), the cross-linking reaction is carried out under nitrogen protection and stirred at 50-80° C. for 1-3 hours.

[0013] Furthermore, the step (3) specifically comprises immersing the functionalized aluminum silicate nanofiber membrane in a methanol solution containing zinc nitrate hexahydrate and 2-methylimidazole to carry out an in-situ growth reaction of ZIF-8, wherein the dosage ratio of 2-methylimidazole, zinc nitrate hexahydrate and the functionalized aluminum silicate nanofiber membrane is 1 g: (1-1.5) g: (3-7) g.

[0014] Furthermore, the ZIF-8 in-situ growth reaction in step (3) is carried out by stirring at room temperature for 5 to 10 hours. After the reaction, the sample is taken out, washed thoroughly with deionized water, and dried to obtain a ZIF-8 / aluminum silicate nanofiber composite membrane.

[0015] Another technical solution of the present invention is a ZIF-8 / aluminum silicate nanofiber composite membrane, which is prepared by the aforementioned method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane.

[0016] Furthermore, the weight of the ZIF-8 / aluminum silicate nanofiber composite membrane is no more than 15 g / m 2 .

[0017] The present invention first utilizes the esterification reaction between the hydroxyl group on the surface of aluminum silicate nanofiber and the carboxyl group in the amino acid to introduce a large amount of amino groups on the surface of the aluminum silicate nanofiber. Subsequently, ethylenediaminetetraacetic acid dianhydride is used as a bridge to achieve effective crosslinking between the aminoated aluminum silicate nanofibers. Thus, on the one hand, a nanofiber membrane with excellent structural stability can be prepared by a simple vacuum filtration technique, and on the other hand, a large amount of N and O atoms containing lone pair electrons introduced during the crosslinking process provide abundant binding anchor points for the growth of ZIF-8, greatly promote the subsequent in-situ growth of ZIF-8 on the surface of the nanofiber membrane, and form a dense ZIF-8 nano-covering layer.

[0018] The advantages of the present invention compared with the prior art are:

[0019] The present invention not only enhances the overall stability and structural integrity of the aluminum silicate nanofiber membrane through the amino modification strategy and ethylenediaminetetraacetic acid dianhydride crosslinking technology, but also provides abundant active sites (a large number of N and O atoms rich in lone pair electrons) for the growth of ZIF-8, so that ZIF-8 can be in situ grown on the aluminum silicate nanofiber membrane in the form of a denser nanolayer, effectively inhibiting the aggregation of nanoparticles and greatly increasing the loading capacity of ZIF-8. The composite nanomembrane prepared by the present invention combines the excellent adsorption performance of aluminum silicate nanofibers with the adsorption capacity of ZIF-8, significantly improves the adsorption capacity of heavy metals, and can maintain its morphology and performance under various environmental conditions, overcomes the difficulty of traditional nanomaterial powder forms in recycling and reuse in applications, facilitates recycling and reuse, and greatly improves the practicality and economic benefits of the material. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.

[0021] Example 1

[0022] A method for preparing a ZIF-8 / aluminum silicate nanofiber composite membrane comprises the following steps:

[0023] (1) Weigh 1 g of aluminum silicate nanofibers and add them to 200 ml of dimethyl sulfoxide. Ultrasonic dispersion is then performed. Then, 1 g of alanine and 0.15 g of p-toluenesulfonic acid are added. The mixture is stirred and reacted at 60 °C for 4 h. After the reaction, the mixture is filtered and repeatedly washed with deionized water. After drying, the amino aluminum silicate nanofibers are obtained.

[0024] (2) Add 1g of the above amino-silicon aluminum nanofibers to 600ml of N , N-dimethylformamide, ultrasonically dispersed evenly, added 0.4g of ethylenediaminetetraacetic anhydride, and stirred at 60℃ for 2h under nitrogen protection. After the reaction, a certain volume of the reaction solution (33.7ml) was taken for suction filtration to form a membrane, and repeatedly washed with deionized water, dried in a drying vessel for 10h, and the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10cm and a gram weight of 10g / m 2 Free-standing functionalized aluminum silicate nanofiber membrane.

[0025] (3) 15.7 mg of zinc nitrate hexahydrate and 15.7 mg of 2-methylimidazole were stirred and dissolved in 300 ml of methanol solution, and the functionalized aluminum silicate nanofiber membrane was immersed in the solution. After reacting for 7 hours, the membrane was taken out, washed thoroughly with deionized water, and dried to obtain a ZIF-8 / aluminum silicate nanofiber composite membrane.

[0026] The adsorption performance test experiment of the ZIF-8 / aluminum silicate nanofiber composite membrane of this embodiment 1 is as follows:

[0027] Prepare 100 mL of an aqueous solution with a lead ion concentration of 100 mg / L (lead nitrate as a reagent) in a flask, adjust the solution pH to 7 with 0.1 M NaOH, add the prepared ZIF-8 / aluminum silicate nanofiber composite membrane, and then adsorb for 3 hours at 200 rpm in a constant temperature oscillator at 30 ° C. After adsorption, take the upper clear liquid, and use ICP-OES to determine the concentration of lead ions in the clear liquid. The adsorption amount of lead ions by the adsorbent material is calculated by the following formula ( Q , mg / g), and the results are listed in Table 1.

[0028] Q =( C 0 - C t ) V / M

[0029] Q is the adsorption amount (g / g); C 0 is the initial concentration of heavy metal ions (mg / L); C t is the concentration of heavy metal ions after adsorption (mg / L); V is the volume of the solution (L); M is the mass of the adsorbent (mg).

[0030] Example 2

[0031] The difference between this example and example 1 is that 0.5 g of alanine is added in step (1) of this example. The adsorption performance of the product was measured according to the adsorption performance experiment of the product in example 1, and the results are listed in Table 1.

[0032] Example 3

[0033] The difference between this example and example 1 is that 2 g of alanine is added in step (1) of this example. The adsorption performance of the product was measured according to the adsorption performance experiment of the product in example 1, and the results are listed in Table 1.

[0034] Example 4

[0035] The difference between this embodiment and embodiment 1 is that 0.2 g of ethylenediaminetetraacetic acid dianhydride is added in step (2) of this embodiment, and 39.3 ml of the reaction solution is filtered to form a membrane after the cross-linking reaction. The adsorption performance of the product is measured according to the adsorption performance experiment of the product in embodiment 1, and the results are listed in Table 1.

[0036] Example 5

[0037] The difference between this embodiment and embodiment 1 is that 0.6 g of ethylenediaminetetraacetic acid dianhydride is added in step (2) of this embodiment, and 29.5 ml of the reaction solution is filtered to form a membrane after the cross-linking reaction. The adsorption performance of the product is measured according to the adsorption performance experiment of the product in embodiment 1, and the results are listed in Table 1.

[0038] Example 6

[0039] The difference between this embodiment and embodiment 1 is that in step (3) of this embodiment, 11.2 mg of zinc nitrate hexahydrate and 11.2 mg of 2-methylimidazole are stirred and dissolved in 300 ml of methanol solution. The adsorption performance of the product is measured according to the adsorption performance experiment of the product in embodiment 1, and the results are listed in Table 1.

[0040] Example 7

[0041] The difference between this embodiment and embodiment 1 is that in step (3) of this embodiment, 26.2 mg of zinc nitrate hexahydrate and 26.2 mg of 2-methylimidazole are stirred and dissolved in 300 ml of methanol solution. The adsorption performance of the product is measured according to the adsorption performance experiment of the product in embodiment 1, and the results are listed in Table 1.

[0042] Example 8

[0043] The difference between this embodiment and embodiment 1 is that: in step (2) of this embodiment, 16.9 ml of the cross-linking reaction solution is filtered to form a membrane, and a membrane with a diameter of 10 cm and a gram weight of 5 g / m 2 In step (3) of this embodiment, 7.9 mg of zinc nitrate hexahydrate and 7.9 mg of 2-methylimidazole were stirred and dissolved in 300 ml of methanol solution. The adsorption performance of the product was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0044] Example 9

[0045] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, 50.6 ml of the reaction solution is filtered to form a membrane, and a membrane with a diameter of 10 cm and a gram weight of 15 g / m 2 In step (3) of this embodiment, 23.6 mg of zinc nitrate hexahydrate and 23.6 mg of 2-methylimidazole were stirred and dissolved in 300 ml of methanol solution. The adsorption performance of the product was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0046] Example 10

[0047] A ZIF-8 / aluminum silicate nanofiber composite membrane and a preparation method thereof, comprising the following steps:

[0048] (1) Weigh 1 g of aluminum silicate nanofibers and add them to 200 ml of dimethyl sulfoxide. Ultrasonic dispersion is then performed. Then, 1 g of glutamic acid and 0.15 g of p-toluenesulfonic acid are added. The mixture is stirred and reacted at 80 °C for 3 h. After the reaction, the mixture is filtered and repeatedly washed with deionized water. After drying, the amino aluminum silicate nanofibers are obtained.

[0049] (2) Add 1g of the above amino-silicon aluminum nanofibers to 600ml of N , N -dimethylformamide, ultrasonically dispersed evenly, added 0.4g of ethylenediaminetetraacetic anhydride, and stirred at 80℃ for 1h under nitrogen protection. After the reaction, a certain volume of the reaction solution (33.7ml) was taken for suction filtration to form a membrane, and repeatedly washed with deionized water, dried in a drying container for 10h, and the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10cm and a gram weight of 10g / m 2 Free-standing functionalized aluminum silicate nanofiber membrane.

[0050] (3) 15.7 mg of zinc nitrate hexahydrate and 15.7 mg of 2-methylimidazole were stirred and dissolved in 300 ml of methanol solution, and the functionalized aluminum silicate nanofiber membrane was immersed in the solution. After reacting for 7 hours, the membrane was taken out, washed thoroughly with deionized water, and dried to obtain a ZIF-8 / aluminum silicate nanofiber composite membrane.

[0051] Comparative Example 1

[0052] Disperse 1g of aluminum silicate nanofibers in 600ml N , N - dimethylformamide, ultrasonically dispersed uniformly, 47.1 ml of the dispersion was filtered to form a membrane, washed repeatedly with deionized water, dried in a drying vessel for 6 hours, and the sample membrane was peeled off from the filter membrane to obtain a membrane with a diameter of 10 cm and a gram weight of 10 g / m2 Self-supported pure aluminum silicate nanofiber membrane.

[0053] Comparative Example 2

[0054] According to step (1) of Example 1, amino-modified aluminum silicate nanofibers were prepared, and then 1 g of amino-modified aluminum silicate nanofibers were dispersed in 600 ml N , N - dimethylformamide, ultrasonically dispersed uniformly, 47.1 ml of the dispersion was filtered to form a membrane, washed repeatedly with deionized water, dried in a drying vessel for 6 hours, and the sample membrane was peeled off from the filter membrane to obtain a membrane with a diameter of 10 cm and a gram weight of 10 g / m 2 Self-supporting amino-modified aluminum silicate nanofiber membrane.

[0055] Comparative Example 3

[0056] A self-supporting functionalized aluminum silicate nanofiber membrane was prepared according to steps (1) and (2) in Example 1. However, no ZIF-8 nanolayer was in situ grown on the surface of the fiber membrane.

[0057] Comparative Example 4

[0058] According to the steps in Comparative Example 1, a 10 cm diameter and a 10 g / m 2 The self-supporting pure aluminum silicate nanofiber membrane was then immersed in 300 ml of a solution containing 15.7 mg of zinc nitrate hexahydrate and 15.7 mg of 2-methylimidazole methanol, and after reacting for 7 hours, the membrane was taken out, washed thoroughly with deionized water, and dried to obtain a ZIF-8 / pure aluminum silicate nanofiber composite membrane.

[0059] Comparative Example 5

[0060] According to the steps in Comparative Example 2, a 10 cm diameter and a 10 g / m 2 The self-supporting amino aluminum silicate nanofiber membrane was then immersed in 300 ml of a solution containing 15.7 mg of zinc nitrate hexahydrate and 15.7 mg of 2-methylimidazole methanol, and after reacting for 7 hours, the membrane was taken out, washed thoroughly with deionized water, and dried to obtain a ZIF-8 / amino aluminum silicate nanofiber composite membrane.

[0061] Table 1 Adsorption amount of lead ions by the adsorption films prepared in Examples 1-10 and Comparative Examples 1-5

[0062]

[0063] The results of the comparative examples and comparative examples show that the ZIF-8 / aluminum silicate nanofiber composite membrane prepared by the present invention not only cleverly combines the rich active functional groups of the ZIF-8 nanolayer and the excellent physical structure characteristics of the aluminum silicate nanofiber membrane, but also realizes the strong combination and synergistic effect of the two in adsorption performance, so that it has very excellent adsorption performance for lead ions. Further, through the comparison between Examples 1, 8, and 9, it can be seen that although increasing the mass of the membrane (mainly by increasing the thickness of the membrane rather than the diameter) can intuitively provide more adsorption sites, the increase in thickness reduces the diffusion rate of ions in the membrane, that is, the permeability decreases, thereby limiting the opportunity for metal ions to effectively contact and adsorb on the active sites to a certain extent, ultimately resulting in the actual adsorption amount not being as significant as expected, and even showing a downward trend.

Claims

1. A method for preparing a ZIF-8 / aluminum silicate nanofiber composite membrane, characterized in that: The following steps are involved: (1) Modifying aluminum silicate nanofibers with amino acids to obtain amino-modified aluminum silicate nanofibers, specifically, dispersing the aluminum silicate nanofibers in dimethyl sulfoxide, uniformly dispersing by ultrasonication, and then sequentially adding amino acids and p-toluenesulfonic acid for stirring reaction, wherein the amount ratio of aluminum silicate nanofibers to amino acids is 1 g: (0.5-2) g; (2) cross-linking and modifying the amino-modified aluminum silicate nanofibers by ethylenediaminetetraacetic acid dianhydride, then filtering and forming a membrane, and washing the membrane thoroughly to obtain a functionalized aluminum silicate nanofiber membrane; (3) In situ growing a ZIF-8 nanolayer on the surface of the functionalized aluminum silicate nanofiber membrane, and obtaining a ZIF-8 / aluminum silicate nanofiber composite membrane after drying.

2. The method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The stirring reaction in step (1) is to stir the reaction liquid at 50-80° C. for 3-6 hours, and after the reaction, the reaction is filtered, repeatedly washed with deionized water, and dried to obtain the amino-containing aluminum silicate nanofibers.

3. The method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The amino acid is one of glycine, alanine, valine, leucine, aspartic acid and glutamic acid.

4. The method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The step (2) specifically comprises dispersing the amino aluminum silicate nanofibers in ‌N, N-dimethylformamide, uniformly dispersing by ultrasonication, and adding ethylenediaminetetraacetic acid dianhydride to carry out a cross-linking reaction, wherein the amount ratio of the amino aluminum silicate nanofibers to ethylenediaminetetraacetic acid dianhydride is 1 g: (0.2-0.6) g.

5. The method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 4, characterized in that: The cross-linking reaction in step (2) is carried out under nitrogen protection and stirred at 50-80° C. for 1-3 hours.

6. The method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The step (3) specifically comprises immersing the functionalized aluminum silicate nanofiber membrane into a methanol solution containing zinc nitrate hexahydrate and 2-methylimidazole to carry out an in-situ growth reaction of ZiF-8, wherein the dosage ratio of 2-methylimidazole, zinc nitrate hexahydrate and the functionalized aluminum silicate nanofiber membrane is 1 g: (1-1.5) g: (3-7) g.

7. The method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 6, characterized in that: In the step (3), the ZIF-8 in-situ growth reaction is carried out by stirring at room temperature for 5 to 10 hours. After the reaction, the sample is taken out, fully washed with deionized water, and dried to obtain a ZIF-8 / aluminum silicate nanofiber composite membrane.

8. A ZIF-8 / aluminum silicate nanofiber composite membrane, characterized in that: The composite membrane is prepared by the method for preparing the ZIF-8 / aluminum silicate nanofiber composite membrane according to any one of claims 1 to 7.

9. The ZIF-8 / aluminum silicate nanofiber composite membrane according to claim 8, characterized in that: The weight of the ZIF-8 / aluminum silicate nanofiber composite membrane does not exceed 15 g / m 2 .

Citation Information

Patent Citations

  • Preparation method of MOFs-chitosan nanofiber composite membrane

    CN109021264A

  • Preparation method and application of modified ZIF-8 / GO composite membrane

    CN109529779A